Four-color communism : comic books and contested power in the German Democratic Republic - Eedy, Sean (Berghahn, 2021)
"As with all other forms of popular culture, comics in East Germany were tightly controlled by the state. Comics were employed as extensions of the regime's educational system, delivering official ideology so as to develop the "socialist personality" of young people and generate enthusiasm for state socialism. The East German children who avidly read these comics, however, found their own meanings in and projected their own desires upon them. Four-Color Communism gives a lively account of East German comics from both perspectives, showing how the perceived freedoms they embodied created expectations that ultimately limited the regime's efforts to bring readers into the fold"--